2017
DOI: 10.1515/intag-2016-0049
|View full text |Cite
|
Sign up to set email alerts
|

How enzymes are adsorbed on soil solid phase and factors limiting its activity: A Review

Abstract: A b s t r a c t. A majority of biochemical reactions are often catalysed by different types of enzymes. Adsorption of the enzyme is an imperative phenomenon, which protects it from physical or chemical degradation resulting in enzyme reserve in soil. This article summarizes some of the key results from previous studies and provides information about how enzymes are adsorbed on the surface of the soil solid phase and how different factors affect enzymatic activity in soil. Many studies have been done separately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(50 citation statements)
references
References 114 publications
3
44
0
1
Order By: Relevance
“…This also helps to explain the relatively similar sorption onto pine biochar, despite its much larger surface area. An enzyme will sorb more to a negatively charged mineral surface when the enzyme is at its isoelectric point, and possesses no charge [24,38]. This was observed previously with a wood biochar and BG at a pH of 5, close to its isoelectric point [27].…”
Section: Enzyme Sorptionsupporting
confidence: 61%
“…This also helps to explain the relatively similar sorption onto pine biochar, despite its much larger surface area. An enzyme will sorb more to a negatively charged mineral surface when the enzyme is at its isoelectric point, and possesses no charge [24,38]. This was observed previously with a wood biochar and BG at a pH of 5, close to its isoelectric point [27].…”
Section: Enzyme Sorptionsupporting
confidence: 61%
“…Certain enzymes from specialized bacteria and fungi have been identified by researchers that can catalyze a number of oxidative and hydroxylation reactions, depolymerize the phenolic and non-phenolic lignin polymer, and also mineralize the insoluble lignin. The orientation, adsorption, and diffusion of the ligninolytic enzymes in the soil solid phase affect the lignin degradation in soil [31]. In laboratory studies, the impact of soil particle size on soil respiration was observed by Datta et al, which can, in turn, affect lignin degradability in soil [32].…”
Section: Lignin Degradation In Soilmentioning
confidence: 96%
“…While the overall relevance of phosphatase enzymes for the hydrolysis of organic P is evident, the relative importance of specific phosphatases for soil organic P hydrolysis is unclear. Several factors determine the availability of both specific phosphatases and specific organic P compounds in soil; their release by soil biota and plants into soil and their degree of stabilization on the soil solid phase (Celi and Barberis, 2005;Datta et al, 2017). Additionally, enzymatic activity may change under different environmental conditions (e.g., temperature or pH).…”
Section: Introductionmentioning
confidence: 99%